2019
DOI: 10.1159/000505625
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated View on Vascular Dysfunction in Alzheimer’s Disease

Abstract: Background: Cerebrovascular disease is a common comorbidity in patients with Alzheimer's disease (AD). It is believed to contribute additively to the cognitive impairment and to lower the threshold for the development of dementia. However, accumulating evidence suggests that dysfunction of the cerebral vasculature and AD neuropathology interact in multiple ways. Vascular processes even proceed AD neuropathology, implicating a causal role in the etiology of AD. Thus, the review aims to provide an integrated vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 215 publications
(272 reference statements)
1
57
0
2
Order By: Relevance
“…We used holo-nano-XPCT to achieve single plaque details, such as the presence of neurites – appearing as black dense spots – inside and around the plaque corona ( Figure 6B ). In AD, the deposition of Aβ inside the vessels determines their lumen reduction or even occlusions, as well as wall breakages, culminating in a reduced cerebral blood flow ( Klohs, 2019 ). Holo-nano-XPCT can reveal fine details from a 3D volume ( Figure 7 , left panel) to capillary and cell levels.…”
Section: Resultsmentioning
confidence: 99%
“…We used holo-nano-XPCT to achieve single plaque details, such as the presence of neurites – appearing as black dense spots – inside and around the plaque corona ( Figure 6B ). In AD, the deposition of Aβ inside the vessels determines their lumen reduction or even occlusions, as well as wall breakages, culminating in a reduced cerebral blood flow ( Klohs, 2019 ). Holo-nano-XPCT can reveal fine details from a 3D volume ( Figure 7 , left panel) to capillary and cell levels.…”
Section: Resultsmentioning
confidence: 99%
“…A lower clotting time (aPTT, PT), bilirubin, and lactate and greater platelet count, prealbumin, and cholesterol levels in female AD patients may provide a multivariate way to identify potential AD phenotype in females. Prior studies have shown high thrombin 97, 98 , abnormalities of hemostasis 99, 100 , and abnormal platelet activation 101–,103 in AD patients that may contribute to a pro-thrombotic state in AD 104 , leading to microinfarcts and cerebrovascular dysfunction 105, 106 , although sex specific associations have not been studied previously. Furthermore, control sex phenotype may demonstrate protective labs or biomarkers that decrease risk of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In DR inhibition of the vascular inflammatory receptor ICAM-1 leads to reduced leukostasis and vascular leakage ( 70 ), and VEGF-A leads to increased levels of ICAM-1 in the vasculature ( 71 ). In AD low level chronic vascular inflammation is also present ( 72 ). This is supported by recent single-nucleus transcriptome analysis of endothelial cells, which have shown an increased level of genes involved in vascular inflammation in aged healthy humans ( 50 ), and patients with AD ( 54 ).…”
Section: Discussionmentioning
confidence: 99%